2019
DOI: 10.1111/ajr.12467
|View full text |Cite
|
Sign up to set email alerts
|

Project to improve storage, access and incorporation of advance care plans in a regional Australian hospital

Abstract: Problem: Despite acknowledged benefits, the impact of advance care planning on usual care is inconsistent. Design: Quality improvement study. Setting: A Western Australian regional hospital. Key measures for improvement: This project aimed to create a system for storing, accessing and incorporating advance care planning documents in clinical care. Strategies for change: Interventions over 18 months addressed four areas: medical records processes for receiving and processing advance care planning documents; inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…To illustrate, a recent Australian study demonstrated how a relatively simple intervention involving new clerical processes, minor modifications to the electronic patient administration system and clinician education markedly improved the number, accessibility, and recognition of ACP documents within a regional public health service. 36 Our findings also suggest there is an opportunity for system-level improvements to support the accessibility of ACP documentation in Australian health services. Given the current variability in systems for storing, retrieving, and accessing ACP documentation in Australia, 22 the use of a centralized e-health record system may improve the availability, transferability, and secure storage of ACP documentation.…”
Section: Discussionmentioning
confidence: 62%
“…To illustrate, a recent Australian study demonstrated how a relatively simple intervention involving new clerical processes, minor modifications to the electronic patient administration system and clinician education markedly improved the number, accessibility, and recognition of ACP documents within a regional public health service. 36 Our findings also suggest there is an opportunity for system-level improvements to support the accessibility of ACP documentation in Australian health services. Given the current variability in systems for storing, retrieving, and accessing ACP documentation in Australia, 22 the use of a centralized e-health record system may improve the availability, transferability, and secure storage of ACP documentation.…”
Section: Discussionmentioning
confidence: 62%
“…Electronic medical records systems with functionality in communicating ACD documentation between healthcare settings play an important role in ensuring concordance between preferred and actual care. 30 Telehealth approaches may help in overcoming barriers to inclusive, family based ACP discussions due to physical distancing and limitations on visitation. 31 This rapid health system and community capacity building (particularly in the area of video-conferencing) will likely have permanent impacts on healthcare delivery, including opportunities to improve ACP for people with chronic diseases and those living in rural and remote areas.…”
Section: Leveraging Societal Changementioning
confidence: 99%
“…National registries and health records, such as the National Health Service Digital in the United Kingdom or My Health Record in Australia, may assist in bridging this gap in communication [ 29 , 30 ] but as at March 2020, the number of ACP documents uploaded to My Health Record was 0.11% (26,920/22,740,000) [ 31 ]. Within countries, there are inconsistencies in where and how ACP documents are stored within electronic health records [ 32 ā€“ 34 ]. Electronic record system alerts can be used to inform hospital staff that a patient file includes an ACP document [ 34 , 35 ].…”
Section: Introductionmentioning
confidence: 99%
“…Within countries, there are inconsistencies in where and how ACP documents are stored within electronic health records [ 32 ā€“ 34 ]. Electronic record system alerts can be used to inform hospital staff that a patient file includes an ACP document [ 34 , 35 ]. Defining this ā€˜missing linkā€™ in the ACP process may assist in more peopleā€™s preferences being known and respected during end-of-life care.…”
Section: Introductionmentioning
confidence: 99%